Gagates: A Magical Gemstone - Mastrocinque, Attilio (Acta Classica Universitatis Scientiarum Debreceniensis, 2024)
The jet stone was used for amulets from antiquity to modern times. Legends and beliefs concerning it flourished. It is black and, being similar to amber, could be burned to obtain a smoke used for magical and medical purposes. Some religious ceremonies used it for attracting snakes. It was often confused with other stones, such as aetites and serpentine and even with agate because it was also called antachates.